2004
DOI: 10.1038/sj.bjc.6601900
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus: evidence of an association with Hodgkin's disease

Abstract: The quest for an infectious agent that may account for cases of Hodgkin's disease (HD) especially in young adults has proven vain until lately. We have recently reported findings that suggested the presence of measles virus (MV) antigens and MV RNA in the tissues of patients with HD. Support for an association between MV and HD has been provided by recent epidemiological findings relating the occurrence of HD to exposure to measles in pregnancy and the perinatal period. We now present further evidence of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 39 publications
(33 reference statements)
0
60
1
1
Order By: Relevance
“…Few subjects reported measles over the age of 10 years and subjects infected over the age of 4 years appeared to have reduced risk of young adult cHL. These data, therefore, do not support the speculation 21 that late exposure to MV, which can occur in unvaccinated patients and in vaccinated young adult patients with waning immunity, 39 is associated with an increased risk of young adult HL. When we considered age at MV infection, Ôall casesÕ and EBV2ve cHL cases in the young adult age group were significantly more likely to report measles below the age of 5 years when compared to those who reported measles at older ages.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Few subjects reported measles over the age of 10 years and subjects infected over the age of 4 years appeared to have reduced risk of young adult cHL. These data, therefore, do not support the speculation 21 that late exposure to MV, which can occur in unvaccinated patients and in vaccinated young adult patients with waning immunity, 39 is associated with an increased risk of young adult HL. When we considered age at MV infection, Ôall casesÕ and EBV2ve cHL cases in the young adult age group were significantly more likely to report measles below the age of 5 years when compared to those who reported measles at older ages.…”
Section: Discussioncontrasting
confidence: 59%
“…20,21 Although cautious about attributing a causal role to the virus, they suggested that the time was ripe for an international effort to verify (or refute) their findings. 20 We therefore examined this association using both epidemiological and laboratory-based methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 There are also recent indications that measles virus and TT viruses may be involved in HL pathogenesis, but this needs further confirmation. 22,23 Furthermore, over the last years several aberrantly expressed proteins and inappropriately activated signalling pathways have been identified, which are important for HRS cell phenotype, survival and proliferation, but for which the causing genetic alterations are still unknown. The following discussion focuses on recent advances in 4 central fields of classical HL research, namely the aberrant activation of multiple signalling pathways in HRS cells, antiapoptotic mechanisms important for HRS cell survival, the pathogenesis of composite lymphomas and new insights into the role of EBV in HRS-cell pathogenesis and the survival of crippled GC B cells.…”
mentioning
confidence: 99%